DAMPAK HICARD DAN DIMENSI KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN HYPERMART - Arum Purbohastuti (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This aim of the research is to identify the impact of the hicard clubcard and services quality (tangibles, emphaty, reliability, responsiveness and assurance) on customer loyalty in Cilegon City. This research method using quantitative research methods was used based on 60 questionnaires conducted with randomly selected customers in Hypermart in 2016. Output in Coefficients it can be concluded that the variables that positively affects brand loyalty is Hicard with the calculated value 1.836> 1.67 (t table) and tangibles positive effect on loyalty to t value of 1.765> 1.67. While other variables have no effect on consumer loyalty Hypermart Cilegon.